Hubungan antara Emotional Branding dengan Loyalitas Merek pada Konsumen Kartu Seluler XL - Mirza Mirza; Anglina Febrina (UIN Sunan Kalijaga, 2016)
Brand loyalty has become essential to the life of a company that every telecommunications company in Indonesia are trying to create a variety of innovations in order to always excel in the market. However, to become the number one provider in the market needed workable marketing strategy is to create a brand that can connect with the emotions of consumers so as to create consumer brand loyalty. The purpose of this study was to investigate the relationship between emotional branding on consumer brand loyalty card mobile XL. The sample in this study was 271 XL mobile card consumers in Banda Aceh aged 13-30 years with a mobile card usage period for at least 3 months. Data in this research was collected using a scale to brand loyalty based on the theory from Schiffman and Kanuk (2004) and for emotional branding based on the theory from Gobẻ (2005). Methods of data collection in this study using a scale giving emotional branding and brand loyalty. Pearson correlation analysis was used to analyze the relationship between the two variables of the study. Pearson correlation analysis showed that there is a significant relationship between emotional branding and consumer brand loyalty in mobile cards XL is p = 0.000 and the value of correlation (r) of 0.241.